Association between hours worked in paid employment and diet quality, frequency of eating out and consuming takeaways in the UK. Issue 18 (13th August 2019) - Sam, Lucy; Craig, Tony; Horgan, Graham W; Macdiarmid, Jennie I
Abstract: Objective: To examine associations between hours worked and diet quality, frequency of eating out and consuming takeaways. Design: Data were taken from the National Diet and Nutrition Survey (2008–2014). Associations between hours worked in paid employment and diet quality, assessed using the Diet Quality Index (DQI) and selected foods and nutrients, were tested using linear regression models. Associations between hours worked and frequency of eating out and consuming takeaways were tested using ordinal logistic regression models. All models were adjusted for sex, age, equivalised household income, household composition and household food role. Setting: UK. Participants: Adults ( n 2154) aged 19–64 years in employment. Results: Mean (95 % CI) hours worked per week was 36·1 (35·6, 36·6) and mean DQI score was 41·9 (41·2, 42·5) %. Hours worked was not associated with DQI score, frequency of eating out or consuming takeaways. Hours worked was positively associated with consuming red meat, processed meat and alcohol intake. Adults working more hours had lower intake of fibre but higher total fat and saturated fat intakes if they lived in households with children. Conclusions: Working hours may not be the main factor driving poor-quality diets among this sample of UK adults in employment. Focusing on consumption of foods prepared outside the household may not be the most efficient way to improve diet quality as effort is needed at all levels. Although it is unclear what is driving the differences in nutrient intakes according to household composition, they are important to consider when developing interventions to improve healthy eating.